Prevalence of Oral Mucosal Lesions with Assessment of Renal Parameters Among Industrial Chemical Factory Workers - Muhammad Khalil, Irfan Ahmad, Irfana Hassan, Sadaf Raffi, Misbah Ul Hasan Ghani, Muhammad Azhar Khan (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
This study investigates the prevalence of oral mucosal lesions (OMLs) and assesses renal function parameters among industrial chemical factory workers. A cross-sectional design was employed,involving 200 workers exposed to chemical agents. Clinical oral examinations were conducted to identify OMLs, and blood samples were analyzed for renal function markers, including serum creatinine, blood urea nitrogen (BUN), and estimated glomerular filtration rate (eGFR).